2015
DOI: 10.1371/journal.pone.0121203
|View full text |Cite|
|
Sign up to set email alerts
|

The Human Footprint in Mexico: Physical Geography and Historical Legacies

Abstract: Using publicly available data on land use and transportation corridors we calculated the human footprint index for the whole of Mexico to identify large-scale spatial patterns in the anthropogenic transformation of the land surface. We developed a map of the human footprint for the whole country and identified the ecological regions that have most transformed by human action. Additionally, we analyzed the extent to which (a) physical geography, expressed spatially in the form of biomes and ecoregions, compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 35 publications
0
35
0
8
Order By: Relevance
“…The burgeoning availability of detailed geospatial layers of infrastructure contrasts with the lack of quantification of their effects, which still relies on expert knowledge and is mostly based on single species or local studies (14). As a result, mapping of the area of influence of infrastructure ranges from a few hundred meters (15) up to 50 km (10,11,16,17).…”
mentioning
confidence: 99%
“…The burgeoning availability of detailed geospatial layers of infrastructure contrasts with the lack of quantification of their effects, which still relies on expert knowledge and is mostly based on single species or local studies (14). As a result, mapping of the area of influence of infrastructure ranges from a few hundred meters (15) up to 50 km (10,11,16,17).…”
mentioning
confidence: 99%
“…Mexican arid and semi-arid ecosystems have been historically modified by humans (Challenger et al, 1998;García and Jurado, 2008;González-Abraham et al, 2015). The TA ecoregion is not exempt from this, as observed in the results section (Fig.…”
Section: Tamaulipan (Ta) Semi-arid Ecoregionmentioning
confidence: 64%
“…Land cover in these ecoregions continues to undergo profound changes due to the development of crop and livestock farming: a quarter of the national agricultural products are cultivated in these ecoregions, while one out of three kilograms of meat is produced here (SAGARPA, 2014). Official cartography generated by the Instituto Nacional de Estadística y Geografía (National Institute of Statistics and Geography, INEGI) of Mexico has been essential in monitoring LULCC in Mexico through the years, as reflected by recent efforts to characterize human impacts at the ecoregion level in the country (González-Abraham et al, 2015). In turn, exposure to ECE is monitored by the Centro Nacional de Prevención de Desastres (National Centre for Disaster Prevention, CENAPRED), which generates publicly available geographic information that maps differences in exposure to diverse ECE throughout the territory (CENAPRED, 2012(CENAPRED, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the west coast of the GOC appears to have low levels of land based threats because it is inaccessible and has a low human population density, except for the northern and southern tips of the peninsula where there are rapidly growing developments (Fig. 7b), a trend that continues based on a recent study (Gonzalez-Abraham et al 2015). In contrast, land based threats are much higher along the east coast of the GOC, in part driven by land-based nutrient pollution from farming activities that represent a potential risk to marine areas (Alvarez-Romero et al 2015).…”
Section: Considering Threats and Opportunitiesmentioning
confidence: 93%